2019
DOI: 10.1002/jcp.28830
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–mesenchymal transition in the formation of hypertrophic scars and keloids

Abstract: Abnormal wound healing is likely to induce the formation of hypertrophic scars and keloids, which leads to dysfunction, deformity, and mental problem in the patients.Despite the advances in prevention and management of hypertrophic scar and keloids, the mechanism underlying scar and keloid formation has not been fully elucidated. Recent insights into the role of the epithelial-mesenchymal transition (EMT) in development, wound healing, stem cell regulation, fibrosis, and tumorigenesis have increased our unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 54 publications
1
33
0
3
Order By: Relevance
“…The incidence of HS is between 40 and 70% following surgery and as high as 91% after burns (4, 5). Although HS has been studied extensively in recent years, no practical or specific therapeutic approaches are currently available for HS, partially because the underlying mechanism remains poorly understood (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of HS is between 40 and 70% following surgery and as high as 91% after burns (4, 5). Although HS has been studied extensively in recent years, no practical or specific therapeutic approaches are currently available for HS, partially because the underlying mechanism remains poorly understood (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal scarring, such as hypertrophic scars and keloids, results in a remarkable alteration in appearance and function, and impairs the patient’s quality of life, both physically and psychologically (Van Loey and Van Son, 2003; Finnerty et al, 2016). It has been shown that genetic predisposition and skin injury play an important role in the formation of hypertrophic scars and keloids (Yuan et al, 2019). Different from hypertrophic scar, keloids are wounding-induced fibroproliferative tumor-like human scars.…”
Section: Introductionmentioning
confidence: 99%
“…an endothelial-tomesenchymal transition (Lim et al, 2019;Yuan et al, 2019). Thus, there is a considerable heterogeneity of cell populations, with diverse biosynthetic profiles within keloids.…”
Section: Pathomechanisms Of Keloidsmentioning
confidence: 99%